2017
DOI: 10.5194/acp-17-10535-2017
|View full text |Cite
|
Sign up to set email alerts
|

A quantitative analysis of the reactions involved in stratospheric ozone depletion in the polar vortex core

Abstract: Abstract. We present a quantitative analysis of the chemical reactions involved in polar ozone depletion in the stratosphere and of the relevant reaction pathways and cycles. While the reactions involved in polar ozone depletion are well known, quantitative estimates of the importance of individual reactions or reaction cycles are rare. In particular, there is no comprehensive and quantitative study of the reaction rates and cycles averaged over the polar vortex under conditions of heterogeneous chemistry so f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
78
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(83 citation statements)
references
References 56 publications
(155 reference statements)
5
78
0
Order By: Relevance
“…Having ruled out technical changes to the simulation and to the instrumental sides during this time, it seems as if we can observe a model bias that is known from satellite comparisons at higher altitudes in the dark polar vortices, a problem that is observed by other models as well (Wohltmann et al, 2017;Grooß et al, 2018). Our intercomparison of model and in situ data supports the rationale that chemistry-climate models struggle in reproducing the observed chlorine partitioning in the dark winter months, where some unknown process for HCl removal is lacking.…”
Section: Comparison Of Measured and Clams-modelled Datamentioning
confidence: 92%
See 1 more Smart Citation
“…Having ruled out technical changes to the simulation and to the instrumental sides during this time, it seems as if we can observe a model bias that is known from satellite comparisons at higher altitudes in the dark polar vortices, a problem that is observed by other models as well (Wohltmann et al, 2017;Grooß et al, 2018). Our intercomparison of model and in situ data supports the rationale that chemistry-climate models struggle in reproducing the observed chlorine partitioning in the dark winter months, where some unknown process for HCl removal is lacking.…”
Section: Comparison Of Measured and Clams-modelled Datamentioning
confidence: 92%
“…from the Microwave Limb Sounder (MLS) or the Atmospheric Chemistry Instrument-Fourier Transform Spectrometer (ACE-FTS), do not achieve the high vertical resolution necessary to resolve strong concentration gradients near the tropopause (e.g. Livesey et al, 2017;Mahieu et al, 2008;Wolff et al, 2008). On the other hand, there have been numerous airborne activities in the Arctic LMS, but only a few airborne (Bonne et al, 2000;Wilmouth et al, 2006) or balloon-borne (e.g.…”
mentioning
confidence: 99%
“…The microphysics of Polar Stratospheric Clouds (PSCs) and their impact on the chemistry is taken into account by a simple parameterization as described in Huijnen et al (2016) but with several updates. In its original implementation, the CTM overestimated the loss of HCl by heterogeneous chemistry (in contrast to other models which underestimate the loss of HCl, see Wohltmann et al, 2017;Grooß et al, 2018). Preliminary experiments prior to BRAM2 showed that data assimilation was not able to correct for this bias (not shown).…”
Section: Bascoementioning
confidence: 99%
“…The species shown in Fig. 7 (Wohltmann et al, 2017;Grooß et al, 2018). Note that the BASCOE CTM is based on a relatively simple PSC parameterization and that its parameters have been tuned to improve the model representation (see Sect.…”
mentioning
confidence: 99%
“…However, within the area of the southern polar vortex, severe stratospheric ozone losses have been observed since the late 1970s, especially in September and October (e.g., [3][4][5]). The enhanced depletion has been explained by the chemical reaction between the ozone molecules and man-made chemicals, such as chlorofluorocarbons (CFCs), e.g., [6,7]. The use and manufacture of Along with the above-mentioned global validations, there are much fewer detailed, site-based studies covering the Antarctic continent.…”
Section: Introductionmentioning
confidence: 99%